Complex Narrative Tasks and Students’ Perspectives in Building EFL Communication Habits - Putri, Adinda Anugrah; Ahmad, Yousef Bani; Sumarta (PROJECT (Professional Journal of English Education), 2026)
This study explores how complex narrative tasks implemented within the Task-Based Language Teaching (TBLT) framework building communication habits among EFL students in a senior high school in Jakarta. Using a qualitative case study design, data were collected through classroom observations and semi-structured interviews with students and their English teacher. The analysis revealed four major complexities: vocabulary limitations, grammatical inaccuracies, pronunciation issues, and emotional barriers such as anxiety and low confidence. Despite these challenges, students reflected positively on narrative-based TBLT activities, reporting improvement in vocabulary mastery, pronunciation, and understanding of narrative structure, along with increased confidence and motivation. The findings indicate that consistent engagement in complex narrative tasks not only develops linguistic accuracy and fluency but also encourages reflective and sustainable communication habits. This study highlights the pedagogical value of integrating narrative-based TBLT in EFL speaking classrooms and suggests that teachers design staged tasks with sufficient scaffolding to balance linguistic, cognitive, and affective demands.